The role of receipt and timeliness of treatment in socioeconomic inequalities in lung cancer survival: population-based, data-linkage study. Issue 2 (12th June 2014) - Forrest, Lynne F; Adams, Jean; Rubin, Greg; White, Martin
Abstract : Background: Lung cancer survival is socioeconomically patterned, and socioeconomic inequalities in receipt of treatment have been demonstrated. In England, there are target waiting times for the referral (14 days) and treatment intervals (31 days from diagnosis, 62 days from GP referral). Socioeconomic inequalities in the time intervals from GP referral have been found. Cancer registry, Hospital Episode Statistics and lung cancer audit data were linked in order to investigate the contribution of these inequalities to socioeconomic inequalities in lung cancer survival. Methods: Logistic regression was used to examine the likelihood of being alive 2 years after diagnosis, by socioeconomic position, for 22 967 lung cancer patients diagnosed in 2006–2009, and in a subset with stage recorded (n=5233). Results: Socioeconomic inequalities in survival were found in a multivariable analysis adjusted for age, sex, histology, year, timely GP referral, performance status and comorbidity, with those in the most deprived socioeconomic group significantly less likely to be alive after 2 years (OR=0.77, 95% CI 0.66 to 0.88, p<0.001). When receipt of treatment was included in the analysis, the association no longer remained significant (OR=0.87, 95% CI 0.75 to 1.00, p=0.06). Addition of timeliness of treatment did not alter the conclusion. Patients treated within guideline targets had lower likelihood of two-year survival. Conclusions: Socioeconomic inequalities in survival from lung cancer were statistically explained by socioeconomic inequalities in receipt of treatment, but not by timeliness of referral and treatment. Further research is required to determine the currently unexplained socioeconomic variance in treatment rates.